2016
DOI: 10.3208/jgssp.ind-34
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boundary conditions on earth pressure reduction using EPS Geofoam

Abstract: This paper presents results of small scale physical model tests on an instrumented rigid retaining wall subjected to 1-D shaking and effectiveness of EPS (expanded polystyrene) geofoam to reduce seismic earth pressures. Two different boundary conditions viz., retaining wall with and without hinge at the base were considered during experiments. Initial application of 50 kPa static surcharge, followed by seismic load in the form of a stepped sinusoidal acceleration in the range of 0 to 0.7 g was applied in incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The reductions depend on wave intensity, inclusion characteristics, and the wall flexibility. Whereas, Dave, and Dasaka [20] and Dave et al [21] found out the reduction is about 23% in their experimental investigation.…”
Section: Experimental Researchesmentioning
confidence: 81%
“…The reductions depend on wave intensity, inclusion characteristics, and the wall flexibility. Whereas, Dave, and Dasaka [20] and Dave et al [21] found out the reduction is about 23% in their experimental investigation.…”
Section: Experimental Researchesmentioning
confidence: 81%
“…It was found that provision of ESP geofoam can reduce the maximum seismic thrust on the wall by about 28%. In a similar study, Dave et al [62] found that retaining walls with hinged boundary showed a hydrostatic seismic pressure distribution while fixed walls showed a curvilinear seismic pressure distribution. Ertugrul et al [45,63,64] found that low density geofoam can reduce pressure by up to 50% of the dynamic thrust acting on the wall.…”
Section: Experimental Studiesmentioning
confidence: 88%